Psychological Characteristics of Speech and Emotional Spheres of Students’ Personality - Tsyos’, Yulia (East European Journal of Psycholinguistics, 2015)
The article deals with the concept of emotional intelligence, communicability and speech style of personality. The level of communicability and the psychological characteristics of students’ emotional intelligence have been discovered and analyzed. The levels of both: partial and integral emotional intelligence of the students have been graphically showed. It is reported that a high level of empathy and low of the ability to manage their emotions have been found. The correlations between the parameters of sociability and sex, emotional awareness, the ability to control emotions, self-motivation, empathy and the ability to recognize the emotions of others have been described. It is noted that there are positive relationships between communicability and self-motivation among the students. The frequency of use of psycholinguistic markers, that reflects speech styles (direct – indirect, simple – complex, personal – contextual, instrumental – affective) has been also considered and shown. The most frequency were: the use of pronouns "I" and “we”, expressiveness, verbal exaggeration, straightness, representation vital roles, ignoring stylistic devices, clear expression, the absence of interjection and the use of humor. The study revealed the extent of severity of each style, discovered and described the dominant students’ speech. The study made it possible to better assess the emotional sphere of student’s personality, its features and relationships with communicability. The superiority of individualism, establishing of own needs and low focus on interlocutor in the communicative interaction have been demonstrated.ReferencesAbulhanova-Slavskaya, K. (1981) Lichnostnyj Aspekt Problemy Obshhenija. ProblemaObshhenija v Psihologii [Personal Aspect of Communication. The Issue of Communication inPsychology]. Moscow: Nauka.Andreyeva, I. (2006) Emotsionalnyi intellekt: issledovanie fenomena [Emotionalintelligence: a study of the phenomenon]. Voprosy Psihologii, 3, 78–86.Fetiskin N., Kozlov, V, Manujlov, G. (2002). Socialno-psihologicheskaya DiagnostikaRazvitiya Lichnosti i Malyh Grupp [Socio-Psychological Diagnostics of Personality Developmentand Small Groups Development]. Moscow: Instutute of Psychotherapy.Gudykunst, W. & Ting-Toomey, S. (1988). Culture and Interpersonal Communication.Newbury Park, CA: SageZasiekina L. V. (2012) Movlennievі stylі u novіi paradigmі psiholіngvіstichnogo znannja[Speech styles in the new paradigm of psycholinguistic knowledge]. Psykholіngvіstyka, 9, 48–55.
Keywords: speech style; emotional intelligence; level of communicability; psycholinguistic markers.